An Investigation on Essential Oils of Platychaete aucheri Boiss. as an Endemic Plant in Desert Ecosystems. Issue 2 (3rd March 2016) - Safaeian, Roja; Ghanbarian, G.; Yazdanpanah, Z.
Abstract: Due to the necessity of prevention of desertification, in range renovation programs, the identification of drought resistant plants and also using multiple purposes of such a plant species is extremely important. The expanse and the protection of medicinal plants can be an income source for local people in desert region and also provide part of pharmacy factory requirements. According to phytogeography classification, Platychaete aucheri belongs to the Khalij-Omani region. This endemic shrub of Iran grows at Fars province (near Jahrom and near Firoozabad), Kerman and Hormozgan. In the present research Platychaete aucheri has been considered in regard to phytochemical characteristic. The aerial parts of Pl. aucheri were collected in the flowering stage. The collected dried samples were extracted by hydrodistillation method. The amount and percentage of essential oil components was 1.76%. 48 components representing 91.3% of the total oil were characterized. The results of chemical components analysis of essential oils has been shown that the main identified components are myrtenol (34.66%), borneol (18.17%), trans -verbenol (5.7%), bornyl acetate (4.31%), cis -verbenol (3.29%) and 1, 8-cineole (2.42%), respectively. It seems that borneol, trans verbenol and 1, 8-cineole play as an anti-quality factor in animal feed. This issue confirms non-palatability of Pl. aucheri in the flowering stage. Hence, one of the rangeland management principles is prevention of entrance non-native and exotic livestock to the rangelands with toxic plants.